Implementation of PSAP Number 13 at Arifin Achmad Hospital Riau Province - Arini Arini; Aljufri Aljufri; Serly Novianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
To realize a good governance system, it is necessary to make changes in the field of financial accounting, as well as apply a standard, guidelines, and principles as a reference for every government organization in preparing financial reports. Therefore, the Minister of Finance issued Regulation of the Minister of Finance (PMK) Number 217/PMK.05/2015 concerning the statement of accrual-based Government Accounting Standards (PSAP), namely PSAP No. 13 concerning the presentation of the financial statements of the Public Service Agency (BLU). This BLU / BLUD financial report provides information about the economic resources and obligations of the BLU / BLUD at the reporting date and the flow of economic resources during the current period. Users need this information to evaluate the economic capability of BLU / BLUD in future activities. For that we need a test of the factors that can affect the implementation of PSAP No. 13 of them. This study will examine the effect of Organizational Commitment, Human Resources and Information Systems on the Implementation of PSAP No. 13. This research will be conducted at RSUD Arifin Achmad, Riau Province. The research approach uses quantitative with primary data sources. The test uses multiple regression testing with SPSS 23. The results of statistical tests show that Organizational Commitment and Human Resources (HR) have no significant effect on the implementation of PSAP No. 13, while the Information System has a significant effect on the implementation of PSAP No. 13.